Perceived effect of disability on adolescent siblings of children with an intellectual disability: development of a measure and pilot intervention - Nesa, Monique (Curtin University, 2005)
The effects of disability on individuals, their parents and their family as a whole have been extensively researched. However, the specific effects on siblings have not been given adequate attention by mainstream society until recently. Consequently, few services have been available for siblings in our community. Of the research that has explored sibling needs, most have relied on parental reports or used measures developed for alternate populations measuring more general variables such as psychopathology. This research project is concerned with the development of a self-report measure of Perceived Effect of Disability for teenage siblings (12 -17 years) of children with an intellectual disability and the development and pilot of an intervention that aimed to assist the positive adjustment of teenage siblings. The development of the measure involved three stages. First, an extensive item pool was constructed from past literature with 150 potential items identified. To ensure the validity of the item pool for siblings themselves, a sample of 24 teenage siblings rated the importance of the items and subscales. This reduced the number of items. Next, focus groups were run with an alternate sample of 41 teenage siblings for further evidence that all pertinent issues were included and to explore items identified as having low importance in Stage 1. The last stage involved testing the measure’s psychometric properties with a further 80 siblings. Exploratory factor analyses were conducted to determine the measure’s underlying factor structure. Results identified four factors underlying the measure, Positive Influence of Disability, Family Differences, Worry About What Others Think and Lack of Time With Others, all of which exhibited high internal consistency and test-retest reliability over a six-week period.The final measure included 40 items and included two parts, the impact on family life and the impact on social life for siblings. The issues identified through the development of the Perceived Effect of Disability measure were then used to develop a pilot intervention that aimed to assist the positive adjustment of teenage siblings. The result was a 6-week program, consisting of 90-minute groups covering Sharing My Story, Exploring Differences and Disabilities, Exploring and Communicating Feelings, Coping Skills I, Coping Skills II and Finding Meaning. The impact of the program was piloted with two groups, consisting of 16 teenage siblings (aged 12-17 years). A matched comparison sample was also used to determine if the intervention resulted in improved perceptions of the effect of disability on siblings using the Perceived Effect of Disability (PED) subscales. There was no significant interaction between time and group on any of the PED subscales. A main effect was found for time on the Lack of Time With Others subscale only. The non-significant time x group interaction, however, indicates that the main effect of time on Lack of Time With Others scores applied to both groups. There was no significant change in family functioning or self-esteem from pre to post-test for the intervention group. However, extensive qualitative data provided strong support for the importance of such an intervention for this unique group of individuals in our community.